Pendekatan Pembelajaran Differentiated Instriction Di SD Inpres Liliba - Bernadus, Berthi Christiani; Devidce Mbolik, Margret; Adelheid Wara Lay, Maria; Rosmita Takoi, Maria; Benu, Merlin; Djogo Sena, Nathalia; Melani Lodika Natonis, Sania; Rosalina Bulu, Vera; Bessie, Marfelano (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Differentiated Instruction is a pedagogical approach that focuses on adjusting teaching and learning processes based on students’ readiness levels, interests, and learning styles. This study aims to examine teacher and student readiness, identify various constraints emerging during its implementation, and analyze the impact of Differentiated Instruction within the elementary school environment. The research methodology employed a quantitative approach with a causal design through survey techniques. The research subjects consisted of 4 teachers and 49 students from grades V and VI at UPTD SD Inpres Liliba, Kupang City. Data were collected using a four-point Likert scale questionnaire instrument and subsequently analyzed through descriptive statistics using SPSS software.The results of the study indicate that the readiness levels of both teachers and students fall within the moderate to very good categories, although some respondents still demonstrate sub-optimal readiness, particularly regarding the development of flexible lesson plans. Obstacles in the implementation of differentiated learning were found to be at a moderate level. The primary challenges identified include the wide disparity in students’ cognitive abilities, time constraints in preparing diverse teaching materials, and the complexity of classroom management when facilitating different groups simultaneously. Nevertheless, the implementation of Differentiated Instruction yields a highly positive impact on learning quality. This impact is evidenced by significant increases in learning motivation, sharper conceptual understanding, active participation, and enhanced student self-confidence in completing independent tasks. These findings confirm that differentiated instruction is effective in supporting inclusive education oriented toward individual student needs. Furthermore, this practice aligns with the spirit of the Kurikulum Merdeka implementation, which emphasizes educators’ flexibility in creating relevant and contextual learning experiences in elementary schools. ​Keywords: Differentiated Instruction, teacher and student readiness, learning obstacles, impact of learning, elementary school.